2020
DOI: 10.1371/journal.pbio.3000803
|View full text |Cite
|
Sign up to set email alerts
|

Loss of hepatic aldolase B activates Akt and promotes hepatocellular carcinogenesis by destabilizing the Aldob/Akt/PP2A protein complex

Abstract: Loss of hepatic fructose-1, 6-bisphosphate aldolase B (Aldob) leads to a paradoxical up-regulation of glucose metabolism to favor hepatocellular carcinogenesis (HCC), but the upstream signaling events remain poorly defined. Akt is highly activated in HCC, and targeting Akt is being explored as a potential therapy for HCC. Herein, we demonstrate that Aldob suppresses Akt activity and tumor growth through a protein complex containing Aldob, Akt, and protein phosphatase 2A (PP2A), leading to inhibition of cell vi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 68 publications
3
41
0
Order By: Relevance
“…Previous studies have demonstrated that the AKT signaling pathway was activated in HCC and associated with multiple malignant biological behaviors of HCC, inhibition of AKT signaling inhibits the proliferation and migration of HCC [ 29 , 30 ]. In addition, P53 act as a tumor suppressor gene, lots of studies have shown that promoting P53 signaling could suppress the progression of hepatocellular carcinoma [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that the AKT signaling pathway was activated in HCC and associated with multiple malignant biological behaviors of HCC, inhibition of AKT signaling inhibits the proliferation and migration of HCC [ 29 , 30 ]. In addition, P53 act as a tumor suppressor gene, lots of studies have shown that promoting P53 signaling could suppress the progression of hepatocellular carcinoma [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our recent study has demonstrated that ALDOB interacts with AKT to modulate AKT activity and loss of ALDOB activates AKT and promotes HCC by destabilizing the ALDOB/AKT/PP2A protein complex. ( 23 ) Thus, to dissect the different roles of ALDOB in direct binding with IR or through AKT on the downstream lipogenesis, we used ALDOB R46A and R43A mutants that showed differential propensity for interaction with IR and AKT, respectively (Fig. 1F).…”
Section: Resultsmentioning
confidence: 99%
“…Among the genes in the signature, ALDOB made the greatest contribution to the risk score. Previous studies have shown that the absence of ALDOB leads to the loss of Akt inhibition, promotes the development of cancer and indicates a poor prognosis ( Lian et al, 2019 ; Sun et al, 2019 ; He et al, 2020 ). This seems to be contrary to the conclusions of this study, but there are also studies that support the conclusions of this research.…”
Section: Discussionmentioning
confidence: 99%